Pembelajaran Berbasis Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Keterampilan Menulis Puisi Peserta Didik Kelas X MIA 4 MAN 3 Pekanbaru - Martalena Martalena (Lembaga Anotero Scientific, 2022)
Based on teaching experience in class X MIA 4 MAN 3 Pekanbaru, it was found that students had low scores in writing poetry. This problem cannot be ignored because it can affect the learning process. The Contextual Teaching and Learning (CTL) learning model is assumed to be able to improve the results of understanding writing poetry. The purpose of this research is to describe the process improvement, and the learning outcomes of understanding writing poetry through the Contextual Teaching and Learning (CTL) learning model. This research is a classroom action research conducted in two cycles. Cycle I and cycle II were carried out in three meetings, and one test for each cycle. Each cycle consists of four activities, namely planning, action, observation and reflection. The instruments used in this study were observation sheets, field recording sheets, and tests. Qualitative data were obtained through observation and field notes for both educator and teacher activities learners. Qualitative data were analyzed based on data reduction, data presentation, and drawing conclusions. Quantitative data were obtained through essay tests carried out at the end of the cycle. Quantitative data were analyzed using descriptive statistics. The results of qualitative data analysis show an increase in the learning process. The activeness of educators and students is high in the learning process using the Contextual Teaching and Learning (CTL) learning model. The results of quantitative data analysis show an increase in student learning outcomes. In the pre-cycle, the average value of students' poetry writing skills was below the KKM. After learning with the Contextual Teaching and Learning (CTL) model, the average student score increased above the KKM and completed classically. Improved results are influenced by the right learning model. Thus, it can be concluded that the Contextual Teaching and learning model Learning (CTL). can increase the activity of students which has an impact on increasing learning outcomes in learning to write poetry.